Gold Dowry in Acehnese Traditional Marriage: Das Sein and Das Sollen in Pidie Community Practices - Ikhsan, Muhammad; Hasbi, Husnaini; Ishak, Abdullah (Al-Hiwalah: Journal of Sharia Economic Law, 2025)
Abstract: Dowry in marriage is the right of a wife which is the obligation of the husband, in Acehnese customs the dowry is generally in the form of gold. Dowry known as jeulamee or jeunamee has a different value in each district/city in Aceh, some have a value of 1 (one) may equivalent to 3.3 grams, and some have a value of 1 mayam equivalent to 3 grams. The problem arises when the price of buying and selling gold increases, which makes some people postpone their marriage because gold is getting more expensive daily, plus the dowry that must be prepared ranges from 10-30 mayam. Related to this problem, how do das sein and das sollen Pidie society determine the amount of dowry, and how do the parties decide when the price of buying and selling gold increases. Qualitative research is the method used, focusing on field research as a primary source. The first finding in the practice of the Pidie community, das sein society should have married when they were financially and emotionally ready plus an understanding of religion related to the household to avoid unnecessary conflicts. However, Das Sollen found that some people postpone their marriage because of capital constraints, including the dowry which is not a small amount plus the reception or walimatul ursy which also requires large capital. The family in this problem has different views or opinions on how to deal with this problem, generally, both parties will take a middle path in the form of deliberation to achieve win-win solutions.